Investigating the CO2 uncaging mechanism of nitrophenylacetates by means of fs-IR spectroscopy and quantum chemical calculations - Neumann, Karsten; Mewes, Jan-Michael; Dreuw, Andreas (Physical chemistry, chemical physics, 2011)
Caged compounds are widely utilized for light-triggered control of biological and chemical reactions. In our study we investigated the photo-induced decarboxylation of all three constitutional isomers of nitrophenylacetate (NPA), which can be regarded as caged-CO2. UV-pump/IR-probe spectroscopy was used to directly observe the nascent CO2 in the region of 2340 cm−1. Together with quantum chemical calculations the reaction models for all three components could be obtained. For meta- and para-NPA the main decarboxylation pathway proceeds via a triplet state with a lifetime of 0.2 ns. In the case of ortho-NPA the photodecarboxylation reaction is suppressed by an H+- or H˙-transfer reaction in the excited state as a result of the proximity of the nitro and acetate substituents. Nevertheless, the photodecarboxylation can be investigated due to the isolated spectral position of the CO2 band. The analysis of the data reveals that a weak ultrafast release channel (<300 fs) represents the main photodecarboxylation reaction pathway for ortho-NPA. The detailed understanding of the molecular mechanisms of CO2 uncaging should provide general guidelines for the design of systematically improved nitrobenzyl cages.
Im Titel erscheint die Ziffer 2 tiefgestellt
Gesehen am 14.12.2017